Pengaruh Kualitas Produk dan Penerapan Nilai Islam Tehadap Kepuasan Nasabah Tabungan Mudharabah di Bank Syariah Mandiri Kantor Cabang Pembantu Rancaekek - Endang Cahyanti; Ida Rapida Rapida; Ade Iskandar Nasution (Ma'soem University, 2021)
Based on the results of observations, the background of this research is the fluctuation in the number of mudharabah savings customers in the last 5 years, thus encouraging the authors to determine the effect of product quality and the application of Islamic values ??on customer satisfaction with mudharabah savings at Bank Syariah Mandiri KCP Rancaekek. This study aims to determine how the influence of product quality on customer satisfaction with mudharabah savings at Bank Syariah Mandiri KCP Rancaekek, how the application of Islamic values ??affects customer satisfaction in mudharabah savings at Bank Syariah Mandiri KCP Rancaekek, and to find out how the influence of product quality and the application of Islamic values ??on satisfaction mudharabah savings customers simultaneously at Bank Syariah Mandiri KCP Rancaekek. The object of this study is to measure customer satisfaction in mudharabah savings at Bank Syariah Mandiri KCP Rancaekek by focusing on product quality variables and the application of Islamic values. This type of research is quantitative associative with primary data types and uses data collection techniques in the form of observation, interviews, questionnaires, and literature study. While the sampling technique is non-probability sampling. The population of mudharabah savings customers at Bank Syariah Mandiri KCP Rancaekek amounted to 467 people, the sample used the solvin formula with the results of 82 people. The results showed that there was a significant effect of product quality on customer satisfaction with mudharabah savings at Bank Syariah Mandiri KCP Rancaekek with the results of the t-test where the value of tcount > from ttable (8.604 > 1.664) with an analysis of the coefficient of determination of 55.6%, there was a significant effect. The significance of the application of Islamic values ??on mudharabah savings customer satisfaction at Bank Syariah Mandiri KCP Rancaekek with the results of the t test where t count > t table (14,860 > 1,664) with an analysis of the coefficient of determination of 73.4%, and simultaneously there is a significant effect of product quality and the application of Islamic values ??to customer satisfaction with mudharabah savings at Bank Syariah Mandiri KCP Rancaekek with the F test where the value of fcount > ftable (148.746 > 2.37) with an analysis of the coefficient of determination of 79%.